ANALISIS PERCEPATAN DEGRADASI POME (Palm Oil Mill Effluent) MENGGUNAKAN NITROGEN DAN PHOSPATE DENGAN INTERVAL WAKTU 10 DAN 20 HARI - Jefira Dea Savitri; Arie Ikhawan Saputra; Jubaidi, Jubaidi (Poltekkes Kemenkes Bengkulu, 2024)
Indonesia is one of the palm oil producing countries, The waste produced by palm oil is Palm Oil Mill Effluent (POME). POME is the residual waste water from palm oil waste in the form of a brownish viscous liquid containing water (95-96%), oil (0.6-0.7) and 4-5% total solids. Each production of 1 ton of TBS be formed. about 0.6 to 1 m3 POME. The purpose of this study was to measure the acceleration of POME biodegradation after the administration of various doses of Phosphate and Sampling technique using